Produção e qualidade de sementes de amaranto em função da época de semeadura - Miranda, Débora de Souza (2023)
Amaranth is an important crop for food security due to its high content of essential amino acids, vitamins and mineral salts in leaves and seeds. Little is known about the different components of production systems, such as sowing times and cultivars adapted to different Brazilian biomes. The objective of this work was to identify the behavior of amaranth genotypes, in red yellow latosol in southeastern Goiás, at the Experimental Station of the State University of GoiásUniversidade Universitária de Ipameri, regarding the production and quality of seeds as a function of four sowing times, three in the dry season, with irrigation, and one at the end of the rainy season, without irrigation. Seven genotypes of Amaranthus cruentus were evaluated: Alegria, Aurelia´s Verde, Elena´s Rojo, Golden Giant, Juana's Orange, Opopeo and UEG 01 in four sowing dates (02/24, 03/31, 05/05) of 2021 and (01/12) 2022 in a randomized block experimental design with 4 sessions. Data on plant height at flowering and maturity, seed production per kg ha-1, seed production per plant and panicle length were analyzed. For seed quality, the following analyzes were performed: water content, germination test, acceleration test, germination speed index, weight of 1000 seeds, electrical conductivity and seedling length. The average temperature influenced plant height, but did not have direct autonomy with seed yield, the highest yields occurred with sowing on 02/24/2020, using irrigation, the most productive cultivars were Aurelia´s Verde, BRS Alegria and Elena's Rojo. For seed quality the first, second and fourth seasons were compiled.